'Bubble‐Free' Electrochemical Delamination of CVD Graphene Films. Issue 2 (1st September 2014) - Cherian, Christie Thomas; Giustiniano, Francesco; Martin‐Fernandez, Iñigo; Andersen, Henrik; Balakrishnan, Jayakumar; Özyilmaz, Barbaros
<x xml:space="preserve">Abstract</x> The production of large amounts of hydrogen bubbles, typical of electrochemical delamination methods based on the electrolysis of water, results in mechanical damage to graphene during the delamination, transfer, and drying steps. Here a novel 'bubble‐free' delamination method is introduced which exploits the electrochemical dissolution of native copper oxide at a potential lower than that required for the formation of hydrogen bubbles, enabling the production of defect‐free graphene stack. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>